Strategic Integration of Business Intelligence and Cloud Analytics in SMEs: Drivers of Competitive Advantage and Organizational Performance - Dr. Elias Thorne; Sarah J. Mbedu (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
Introduction: In an increasingly digitized global economy, the ability to leverage data is no longer a luxury for large corporations but a necessity for the survival and growth of Small and Medium-sized Enterprises (SMEs). Despite the proliferation of data generation, many SMEs struggle to translate raw information into actionable strategic assets. Objectives: This study aims to investigate the drivers and impacts of Business Intelligence (BI) and cloud analytics adoption within the SME sector. Specifically, it seeks to understand how BI capabilities enhance organizational performance, marketing effectiveness, and supply chain resilience, effectively creating a sustainable competitive advantage. Methods: The research utilizes a comprehensive theoretical synthesis, grounding its analysis in the Resource-Based View (RBV) of the firm and the Technology-Organization-Environment (TOE) framework. By synthesizing findings from diverse academic sources, the study constructs a holistic model of BI integration tailored to the constraints and opportunities unique to SMEs. Results: The analysis indicates that successful BI adoption in SMEs is contingent upon strong management support and the strategic utilization of cloud computing to mitigate infrastructure costs. Furthermore, the integration of BI is associated with significant improvements in marketing precision through cooperative learning and enhanced supply chain agility. Conclusion: The study concludes that for SMEs to achieve competitive parity or advantage, they must move beyond passive data collection to active, analytics-driven decision-making. Cloud-based platforms offer a viable pathway to access rich features without prohibitive capital expenditure, enabling SMEs to compete on analytics.